Indirect Tensile Stiffness Modulus (ITSM) Analysis of Asbuton Mixture with Used Oil Additives and HDPE - Husni, M Ari; Karyawan, I Dewa Made Alit; Sideman, IAO Suwati (International Journal Labs, 2025)
Asbuton is a natural raw material that has great potential in the development of high-quality asphalt mixtures. To optimize its performance, this study explored the use of additives in the form of used oil and high density polyethylene (HDPE) plastic, which is considered to be able to increase the flexibility, adhesion, and stability of the mixture. The commonly used Marshall method is considered less representative in measuring the indirect tensile stiffness of mixtures which is important for assessing elastic response, so Indirect Tensile Stiffness Modulus (ITSM) testing is used to obtain a more comprehensive picture of the performance of asbutone mixtures. This study uses an AC-BC mixture where the Asphalt content is in a combination of Modified Asphalt (MO) and Oil Asphalt (MI), this modified asphalt uses Asbuton which is given an added ingredient of used Oil and HDPE Plastic, this study uses KAO of 6.0% of the total weight of the test object, from the percentage of this KAO combined with 3 compositions of Asphalt mixture, namely Modified Asphalt with Oil Asphalt. Namely 40% Modified Asphalt: 60% Oil Asphalt, 50% Modified Asphalt: 50% Oil Asphalt, and 60% Modified Asphalt: 40% Oil Asphalt, resulting in consecutive ITSM values of 6124 Mpa, 6286 Mpa, and 6738 Mpa. From these results, it can be concluded that with the increase in the composition of modified asphalt, it increases the rigidity of the test specimen.